2006
DOI: 10.1037/0033-295x.113.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Global model analysis by parameter space partitioning.

Abstract: To model behavior, we need to know how models behave. This means learning what other behaviors a model can produce besides the one generated by participants in an experiment. This is a difficult problem because of the complexity of psychological models (e.g., their many parameters) and because the behavioral precision of models (e.g.,interval-scale performance) often mismatches their testable precision in experiments, where qualitative, ordinal predictions are the norm. Parameter space partitioning is a soluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
119
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 51 publications
0
119
1
Order By: Relevance
“…However, subsequent experiments using eye-movement analysis (a finer grained on-line method) and subsequent TRACE simulations using standard parameters found that the TRACE model was consistent with the behavioral data [50]. Analysis of global model behavior [51] confirmed that TRACE produces the correct behavioral pattern; in fact this analysis showed that TRACE provides a more robust fit to the behavioral data in this case than the autonomous Merge model [4].…”
Section: Subcategorical Mismatchmentioning
confidence: 85%
“…However, subsequent experiments using eye-movement analysis (a finer grained on-line method) and subsequent TRACE simulations using standard parameters found that the TRACE model was consistent with the behavioral data [50]. Analysis of global model behavior [51] confirmed that TRACE produces the correct behavioral pattern; in fact this analysis showed that TRACE provides a more robust fit to the behavioral data in this case than the autonomous Merge model [4].…”
Section: Subcategorical Mismatchmentioning
confidence: 85%
“…Model fitting has recently come under much scrutiny (Kieras & Meyer, 2000;Pitt, Kim, Navarro, & Myung, 2006;Roberts & Pashler, 2000), and it is worth considering whether recent methodological prescriptions for comparing data to parametric theories might be used to address the architecture-strategy credit assignment problem. Framed this way, the question is to what extent some given match to data provides support for the structural invariants of a theory with degrees of freedom.…”
Section: Adopt More Principled Means Of Comparing Data To Theories Wimentioning
confidence: 99%
“…For a thorough presentation of the technical and implementation details of the method, the reader should consult Pitt et al (2006).…”
Section: Parameter Space Partitioningmentioning
confidence: 99%
“…To fill this void, Pitt, Kim, Navarro, and Myung (2006) introduced a model analysis method dubbed parameter space partitioning (PSP). PSP finds all the data patterns that a model can produce in an experimental setting.…”
Section: Parameter Space Partitioningmentioning
confidence: 99%
See 1 more Smart Citation